Study of construction of bypass roads with consideration of environmental and energy indicators - Ugnenko, Yevgeniia; Uzhvieva, Elena; Makovyey, Radu; Puodžiukas, Virgaudas (International Conference “Environmental Engineering”, 2017)
Determination of the radii of circular round-about highways and the corner of their unlocking is considered in the given article. To determine the radius of circular round about highways it is recommended to use the prime price of motor-car cargo transportations, taking into account the factor of their delivery acceleration for roads which provide different speed modes.